Velocity, distance per stroke and stroke frequency of highly skilled swimmers in 50m freestyle sprint in a 50 and 25m pool - Wirtz, W.; Wilke, K.; Zimmermann, F. (Biomechanics and Medicine in Swimming. Swimming Science VI, 1992)
This study compares distance per stroke, stroke frequency and mean velocity of highly skilled swimmers (n = 7) having raced both in a 25 m and a 50 m pool. Videotapes of the European Championships 1989 (50 m pool) and the ARENA-Meetings (25 m) pool 1989 and 1990 were analysed. Individual differences were found in the kinematic profiles of the variables measured between and within groups. For men, the shorter time in the 25 m pool results came mainly from the better time between 0 and 30 m in the 25 m pool. For women, shorter times in the 25 m pool results mainly from the better time between 20 and 30 m.